Oxygen vacancies induced photoluminescence in SrZnO2 nanophosphors probed by theoretical and experimental analysis - Manju; Jain, Megha; Madas, Saibabu; Vashishtha, Pargam; Rajput, Parasmani; Gupta, Govind; Kahaly, Mousumi Upadhyay; Ozdogan, Kemal; Vij, Ankush; Thakur, Anup (NATURE PORTFOLIO, 2020)
We report, for the first time, the influence of oxygen vacancies on band structure and local electronic structure of SrZnO2 (SZO) nanophosphors by combined first principle calculations based on density functional theory and full multiple scattering theory, correlated with experimental results obtained from X-ray absorption and photoluminescence spectroscopies. The band structure analysis from density functional theory revealed the formation of new energy states in the forbidden gap due to introduction of oxygen vacancies in the system, thereby causing disruption in intrinsic symmetry and altering bond lengths in SZO system. These defect states are anticipated as origin of observed photoluminescence in SZO nanophosphors. The experimental X-ray absorption near edge structure (XANES) at Zn and Sr K-edges were successfully imitated by simulated XANES obtained after removing oxygen atoms around Zn and Sr cores, which affirmed the presence and signature of oxygen vacancies on near edge structure.
Keywords: RAY-ABSORPTION SPECTROSCOPY; CARBON NANOTUBES; ZNO; LUMINESCENCE; NANOSTRUCTURES; CRYSTALLINE; CU; Science & Technology - Other Topics